The Pursuit of Happyness (Umudunu Kaybetme) Filmi Üzerinden Pozitif Psikolojik Sermayeye İlişkin Bir Değerlendirme - Denizli Polat, Adviye Aslı; Dündar, Gönen İlkar (Journal of Business Research - Turk, 2024)
Purpose – The concept of positive psychological capital, has been the subject of research in the related literature in recent years. The competitive and challenging conditions of today's business life and changes in the concept of career related to these conditions underline the importance of the concept even more. This study analyzes the various dimensions of positive psychological capital with the movie titled The Pursuit of Happyness. The study tries to shed light on the importance of positive psychological capital regarding an individual's life and career through the findings obtained by analyzing the movie. Design/methodology/approach – The quantitative research method is used, and the movie is examined as a visual document. The movie was discussed in the context of positive psychological capital, and it created the framework of the analysis. Self-efficacy, hope, resilience, and optimism, the sub-dimensions of positive psychological capital, were determined as the thematic framework. The results obtained from the research were categorized per these themes and associated with the literature. Findings – With the help of the method adopted in this study, the aim was to make positive psychological capital, one of the outstanding concepts of today's positive organizational behavior, more clearly understandable with visual and auditory examples. Findings and evaluations regarding the positive psychological capital and its dimensions were given by quoting the movie. Discussing the positive psychological capital through a movie not only enables the reader to clearly assess the subject, but also shows that this movie can be used as educational material in teaching this subject matter. Discussion – The fact that the movie is based on a real-life story reveals the abstract and concrete aspects of the positive psychological capital with real-life scenes. Additionally, through scenes and dialogues, it provides the points of the movie which could not be highlighted with quantitative research methods. In this regard, it is hoped that this research, as an educational material, can contribute to understanding the concept of positive psychological capital and its dimensions and its multifaceted evaluation with discussion on the movie. This study is thought to be an example for future research and movie analyses on the same subject.